Duy trì nền sản xuất lúa bền vững - Danh, Võ Thành (Tạp chí Khoa học Đại học Cần Thơ, 2004)
ABSTRACT The main objective of the study was to estimate the supply response of rice in Viet Nam. The dynamic adaptive adjustment and rational expectation models were used to select an appropriate supply response model for rice under different price expectation hypotheses. A marketed supply surplus model was then derived from the estimated parameters of these supply response models. Results showed that rice farmers were rational in forming the price expectation behavior, making supply decisions based on information available in the past. The rational expectation supply response model with the cobweb price expectation formation may be considered an appropriate econometric model among the supply response models tested. Results indicated that output supply and marketed surplus were positively responsive to price expectation. As to government programs, policy variables had positive effects on rice production. The institutional factor of household responsibility system had no contribution to rice production improvement as expectation. As a result, other factors involving technological progress and market regulations should be regarded potential tools to sustain rice production. The price expectation played an important role in making decision of rice farmers. An appropriate price policy becomes an alternative way to enhance rice production in the country. Title: Substainability of rice production in Viet nam